Methodological establishment and diagnostic value of a multiplex fluorescent PCR assay for the detection of three fastidious respiratory pathogens - Jingchao Shi; Yijun Zhu; Shuyun Chen; Xiaoyun Shan; Lihong Bo; Kai Shen; Keqiang Chen (PLoS ONE, 2025)
Background Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis are common fastidious bacteria responsible for respiratory tract infections, particularly in children and immunocompromised individuals. Due to their demanding growth requirements, traditional culture methods often yield low sensitivity and delayed results, posing challenges for early and accurate diagnosis. Objective To establish a TaqMan probe-based multiplex fluorescent PCR method for the simultaneous rapid detection and identification of three important respiratory fastidious pathogens: Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis. Methods By designing and optimizing TaqMan probes and primers targeting Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis, the sensitivity, specificity, and reproducibility of the TaqMan probe-based multiplex fluorescent PCR assay were examined. A total of 173 clinical samples which are sputum and alveolar lavage fluid were tested simultaneously using traditional culture methods and multiplex fluorescent PCR assays, and the results were compared for consistency. For samples with inconsistent detection results, targeted high-throughput sequencing (tNGS) was used for confirmation. Results The limit of detection of the TaqMan probe-based multiplex fluorescent PCR method was 100 Copies/ml for Streptococcus pneumoniae, 20 Copies/ml for Haemophilus influenzae, and 50 Copies/ml for Moraxella catarrhalis. The detection rate of the multiplex fluorescent PCR method was in high concordance with traditional culture methods and tNGS in the 173 clinical samples (Kappa = 0.819). The multiplex fluorescent PCR method demonstrated high sensitivity and specificity, detecting more cases of mixed infections. Conclusion The multiplex fluorescent PCR method established in this study provides a powerful tool for rapid and accurate clinical detection of fastidious respiratory pathogens, with significant clinical application value and promotion prospects. This method offers substantial advantages over traditional culture methods in terms of detection speed and sensitivity, particularly in detecting mixed infections, and has significant potential for clinical application and widespread adoption.